Delusional Jealousy (Othello Syndrome) in 67 Patients with Parkinson’s Disease - Kataoka, Hiroshi; Sugie, Kazuma (Frontiers in Neurology, 2018)
Othello syndrome (OS) is a type of paranoid delusional jealousy, characterized by the false absolute certainty of the infidelity of a partner. Because OS has infrequently occurred in patients with PD, the characteristics of OS in PD remain unclear. We reviewed the clinical characteristics of this syndrome in PD. We reviewed 67 patients who had PD with OS. OS was more common in men (45 patients) than in women (22 patients), and it frequently occurred in middle-aged patients. Until the onset of OS, the duration of PD (range, 2 to 19.8 years) and the duration of treatment with PD medications (range, 2 months to 18.5 years) varied. At the onset of OS, cognition was preserved in most patients. 42 of 47 patients had other psychiatric disorders in addition to OS, and 5 patients had isolated OS. Persecutory or other paranoid delusions developed in 34 patients with OS. OS was associated with PD medication in 25 of 26 patients, especially in patients used the dopamine agonists. The dose of the PD medication associated with OS was decreased or these drugs were withdrawn to facilitate the treatment of OS. In most patients, OS disappeared or the severity of OS was reduced. OS is infrequent in patients with PD, but is likely to be easily detected because OS is commonly accompanied by persistent paranoid and sexual delusions. When clinicians encounter such patients, the withdrawal or reduction of dopamine agonists should be attempted, and if necessary, additional treatment with clozapine is recommended.